Biofilter utlization in Leptobarbes hoevenii (Jelawat) fry production system - Jafaruddin, bin Ali (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This study was carried out to determine the effectiveness of using of Eichhornia crassipes, Hydrilla verticil/ata and Pistia stratiotes in intensive Leptobarbes hoevenii fry production system. It was established that the optimum ammonia-nitrogen and orthophosphate absorption between species was achieved with the E. crassipes treatment, followed by the H. verticil/ata and P. stratiotes. The P. stratiotes was later removed in subsequent experiments due to poor ammonia-nitrogen and orthophosphate absorptioflj In optimum density of E. cra . ipes experiment, four levels of E. crassipes density were used, which were 0, 150, 300 and 450 grams. The highest L. hoevenii survival and growth were achieved in the 150 gram E. crassipes treatment. Meanwhile, the highest L. hoevenii fry performance in the four H. verticil/ala density levels was acquired in the 50 gram H. verticil/ata treatment. The highest L. hoevenii fry survival and growth in the four combined biofilter treatments was acquired in the 150 gram E. crassipes treatment. Result showed that the 150 gram E. crassipes with mechanical filter obtained the highest fry growth performance when compared with three other treatments. For the study regarding the fish fry density levels, the highest survival and growth of L. hoevenii fry were achieved at 20 fish fry, which was the lowest density level in this research. Based on the overall results, the best design consisted of the following sequence: the first cycle -the water treatment cycle -the second cycle. The first and second cycles were done for five weeks and the water treatment cycle for two weeks.